"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zona Armonia del Palomar". Tejeda 2th from left. Aguilar next to him. Copied from CNT collection.Series of 4 photos
"La visita del embajador de mexico sr. Tejeda a la colectividad de los campesinos de Barcelona, zona Armonia del Palomar". Tejeda 2th from left. Aguilar next to him. Copied from CNT collection.Series of 4 photos.